Go West Young Man: Self-Selection and Endogenous Property Rights. - Jaworski, Taylor; Wilson, Bart J. (Southern Economic Journal, 2013)
If, as Hume argues, property is a self-referring custom of a group of people, then property rights depend on how that group forms and orders itself. In this article we investigate how people construct a convention for property in an experiment in which groups of self-selected individuals can migrate between three geographically separate regions. To test a hypothesis of Demsetz's, we vary across two treatments the external benefits of migrating. We find that self-selection has a powerful effect on establishing conventions of property and begetting increases in wealth through exchange and specialization. We also find support for the Demsetz hypothesis.